Humanismo cívico: hacia una renovación humanista de la vida política (I) (2007)
It is in general quite evident that something is not working well in current Western democracies.On the one hand, civic apathy is becoming more and more common every day, especially amongyoung people. On the other hand, political scandals have become so common that they are no longerconsidered newsworthy. Even though this situation is discouraging on many fronts, there still remainsa socio-political philosophy with clear Aristotelian roots that has been recently rehabilitated by theSpanish philosopher Alejandro Llano. This philosophy is the Civic Humanism which invites us to re-think democracy once again from a genuinely human point of view, since the essence of Civic Humanismis the fact that people and their essential dignity are of central importance.